Integrative geoarchaeological research on settlement patterns in the dynamic landscape of the northwestern Nile delta. (30th March 2019) - Ginau, A.; Schiestl, R.; Wunderlich, J.
Abstract: Settlement activity in the Nile delta is characterized by its profound connection to the branches of the river Nile. Major ancient settlements were founded next to waterways. The constant shifting of these Nile branches – coming either too close or moving too far away – was a fundamental challenge for settlements. This research focuses on the region around Buto (Tell el-Fara'in) in the northwestern Nile delta. The massive increase in settlements in the Ptolemaic, Roman and in particular late Roman periods (4th c BC – 7th c AD) needs to be connected with a fundamental change in the landscape and the way people interacted with the landscape. A particular challenge to reconstructing the ancient land and waterscape was posed by the regional lack of an indicative modern surface relief. A linear settlement pattern of ancient sites was interpreted as showing the distribution along a defunct river branch. A combination of remote sensing data, in particular a new high resolution DEM based on Tandem-X data, and a program of over thirty cores on the ground, have clarified the landscape, especially its fluvial pattern, and the placements of associated settlements. In the north of the study region, the DEM shows elevated levees of former palaeorivers belonging to a finely ramified subdelta, with all settlements placed on alluvial levees. The corings uncovered different artificial channels and identified ancient natural riverbeds at a deep level but similar depth, suggesting that the streams were active during the occupation of these sites and the ancient settlements were either in direct vicinity of the natural rivers or connected via artificial channels. These artificial channels found in corings next to the settlements show characteristics of slack water regimes. In essence, the massive increase of settlements spread over the northwestern delta in Classical Antiquity was spurred by multiple branches that provided routes of transportation, fresh water for irrigation and good conditions for agriculture on their elevated and fertile levees.